Protecting the Empire's Frontier : Officers of the 18th (Royal Irish) Regiment of Foot during Its North American Service, 1767-1776 - Baule, Steven M., 1966- (Book collections on Project MUSE., 2014)
Protecting the Empire's Frontier tells stories of the roughly eighty officers who served in the 18th (Royal Irish) Regiment of Foot, which served British interests in America during the crucial period from 1767 through 1776. The Royal Irish was one of the most wide-ranging regiments in America, with companies serving on the Illinois frontier, at Fort Pitt, and in Boston, New York, and Philadelphia, with some companies taken as far afield as Florida, Spanish Louisiana, and present-day Maine. When the regiment was returned to England in 1776, some of the officers remained in America on staff as.